Recent Advances in Organ Preservation Solutions and Methods for Using in Liver and Kidney Transplantation - Zahra Jamadi; Parinaz Parhizgar; Ghasem Yazdanpanah; Tahereh Tayebi; Roghayeh Tarasi; Hassan Niknejad (مجله دانشکده پزشکی اصفهان, 2020)
Background: The organ transplantation has been developed due to recent advances in transplantation surgery. The method of preservation and the type of preserving solution are determining factors in the outcome of the transplantations. In this review article, we evaluated the process of organ preservation, and compared the employed storage solutions.